Adsorption of heavy metals by layered double hydroxides grown in situ on Al foam. (24th June 2020) - Kaciulis, S.; Bolli, E.; Varone, A.; Richetta, M.; Narducci, R.; Di Vona, M.L.; Ciotta, E.; Pizzoferrato, R.
Abstract : We investigated the adsorption of heavy metal ions on a nanostructured coating of zinc‐aluminum layered double hydroxides (Zn‐Al LDHs) grown on aluminum foam by one‐step hydrothermal process. This approach aimed to increase the interactive surface and provide a more practical medium for removal of toxic heavy metals from aqueous media. The foam coated with LDH was characterized by using scanning electron microscopy and X‐ray diffraction. After immersion in a copper‐rich water solution, X‐ray photoelectron spectroscopy demonstrated the occurrence of adsorbed copper on the LDH‐coated foam with two oxidation states: particles of metallic copper Cu 0 with oxidized surface Cu +1 . X‐ray diffraction showed the presence of Cu +2 in the LDH structure.